Exploring Students’ Challenges and Strategies on Collaborative Academic Writing - Anggraeni, Candradewi Wahyu; Riadil, Ikrar Genidal; Yuntiawati, Meykke Alvia (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Collaborative academic writing plays a vital role in helping students enhance their academic writing skills. However, the students face challenges in utilizing collaborative academic writing. This study aims to explore the students’ challenges and strategies on collaborative academic writing. Grounded in a qualitative case study, this study took five months for the investigation in an academic writing class. Data was collected through learning artifacts and semi-structured interviews. The data were analyzed using a thematic analysis. The findings reveal that students have cognitive, social, logistical and organizational, and linguistic and proficiency-specific challenges. In addition, the study underscores key strategies to cope with the challenges, for instance, having clear roles in writing, optimizing practical communication tools, using structured timelines for writing, leveraging digital writing tools ethically, and conducting peer review processes. The findings provide valuable insights for educators and students to improve collaborative writing experiences, enhance writing performance, and foster better teamwork. This study contributes to developing the body of knowledge in collaborative writing and academic writing pedagogy.